The Influence of Organizational Culture and Servant Leadership on Employee Loyalty at PT Hiend Digital Media - Andhika Bhanu Bismoko; Uki Yonda Asepta; Peter Remy Yosy Pasla; I Gusti Ngurah Agung Arya Bhakta Narayana (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
The goal of this research is to examine the impact of organizational culture and servant leadership on employee loyalty at PT Hiend Digital Media. This research employs a descriptive quantitative method with saturated sampling as the technique for selecting the sample. The research location is at PT Hiend Digital Media, and the respondents consist of 45 employees who have worked there. The analysis methods used in this study include SPSS 22 for validity, reliability, and classical assumption tests. Multiple linear regression, t-test, f-test, and determination coefficient were employed to test the hypotheses. Based on the results, it can be concluded that organizational culture has a significant positive influence on employee loyalty. However, servant leadership does not significantly influence employee loyalty at PT Hiend Digital Media. The f-test results show that employee loyalty is simultaneously influenced by organizational culture and servant leadership.